Analysing accounting and organisational change: the theoretical development - Abdullah, Zarifah; Abdul Khalid, Siti Nabiha (Inderscience Enterprises Ltd., 2012)
The purpose of this paper is to discuss the development of institutionalist theoretical framework that can be used to analyse the process of accounting and organisational change and the role of human agency.In so doing, the philosophical and methodological approach of the institutional theory and the extension and the contributions made to the neo old institutional economics (OIE) framework by several authors are elaborated.This is followed by a detail explanation of Van der Steen's (2005) framework of institutional change that is offered to provide a more comprehensive explanation of change at the individual and also collective levels.However, the neo OIE framework of accounting and organisational change developed so far such as Burns and Scapens (2000), Seo and Creed (2002) and Van der Steen's (2005) have not considered explicitly the role of leadership in the process of change.Questions such as how do leaders influence their subordinates in getting individuals to change their schema and scripts and in getting the team within organisations to work towards resolving the issues and effectively make successful alterations to the individual and 'organisational' mindset have not been taken into considerations.Thus, this paper proposed refinement to the Van der Steen's (2005) framework by integrating elements of leadership in order to effect change both at the individual and collective levels.